2010
DOI: 10.1103/physrevb.81.024111
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability ofTi2AlCupon oxygen incorporation: A first-principles investigation

Abstract: The phase stability of Ti 2 AlC upon oxygen incorporation has been studied by means of first-principles calculations. Recent experimental observations of this so-called MAX phase ͑M = early transition metal, A = A-group element, and X = C or N͒ show that the characteristic nanolaminated structure is retained upon oxygen incorporation, with strong indications of O substituting for C. Therefore, a solid solution of C and O on the carbon sublattice has been simulated by the so-called special quasirandom structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 69 publications
5
81
1
Order By: Relevance
“…Phase stability calculations at 0 K have been proven successful when it comes to verify existing [12,14,22,26,81,[84][85][86] and, more importantly, predicting new MAX phases and related materials [3,7,25,87]. When it comes to magnetic MAX phases, almost all calculations to date neglect effects from temperature.…”
Section: A Methodsmentioning
confidence: 99%
“…Phase stability calculations at 0 K have been proven successful when it comes to verify existing [12,14,22,26,81,[84][85][86] and, more importantly, predicting new MAX phases and related materials [3,7,25,87]. When it comes to magnetic MAX phases, almost all calculations to date neglect effects from temperature.…”
Section: A Methodsmentioning
confidence: 99%
“…Further details are given in Refs. 10,11 To determine the dynamical stability of the studied ordered structure, we performed phonon calculations using the small displacement method, supercell sizes of at least 3x3x1 unit cells, along with the code Phonopy 12 . Density of states (DOS) and chemical bonding were investigated in terms of projected crystal orbital Hamiltonian populations (pCOHP) which were derived using the LOBSTER program 9,12,13 .…”
Section: Section S2 Computational Detailsmentioning
confidence: 99%
“…X-ray diffraction in combination with analytical transmission electron microscopy, including electron energy-loss spectroscopy and energy dispersive x-ray spectroscopy analysis, revealed that the films were epitaxial (0001)-oriented single-crystals with x up to 0. 16 MAX phases constitute a family of inherently nanolaminated compounds with a general composition of M n+1 AX n , where M denotes an early transition metal, A is an A-group element, and X is C and/or N. 1 Presence of both metallic and covalent bonds between different layers provides a unique combination of metallic and ceramic properties, such as high (anisotropic) conductivity, hardness, and thermal shock resistance. 2 Fascinating MAX phase phenomena range from extreme damage tolerance including reversible deformation 3 over oxidation induced self-healing behavior 4 to stability of nanosheets upon exfoliation.…”
mentioning
confidence: 99%